Wireless networked dynamic control testbed for power converters in smart home applications - Islam, Syed; Maxwell, S.; Park, S.; Zheng, S.; Gong, T.; Han, S. (2017)
© 2017 IEEE. Conventional power converters control pulse width modulation (PWM) signals based on the directly sensed feedback signals or estimated state signals. Recently, information and communication technologies are beginning to integrate power converters into smart grid applications. This paper presents a Hardware-In-The-Loop Testbed using a WirelessHART network for smart home applications in a case study. The main components of the testbed are OP4510 RT-LAB-RCP/HIL systems, Texas Instruments Digital Signal Controllers and AwiaTech wireless modules. In this testbed, wireless based controller is integrated with conventional digital controller. OP4510 is used to simulate power stages of the power converters in real time. Texas Instruments Digital Signal Controllers provide PWM signals from the control loop and communication loop. AwiaTech wireless modules are used to build a WirelessHART network to communicate with power converter from a supervisory program. The case study is to support reactive power in smart home applications using 3 bridgeless unidirectional power factor correction (PFC) converters. For this scenario, supervisor collects reactive power measurement data from the input power node and wirelessly transfers reactive power command values to the home appliances driven by PFC converters. Thus, reactive power demand can be minimized. The experimental result demonstrates the performance of the testbed in different communication delays.